Looking at the Perceived Benefits of Feeding Program in the Eyes of the Stakeholders - Candelanza, Jane; Comighud, Sheena Mae (IJRDO-Journal of Applied Science, 2020)
The study focused on the effects of school-based feeding program in the eyes of the stakeholders conducted on March 2019 to grades 1 to 6 beneficiary pupils, selected teachers, SBFP In-Charge and School Head of Mansagomayon Elementary School, District 4 of Sta. Catalina, Division of Negros Oriental. A descriptive design was used in this study whichd eemed appropriate in the context of this study since the researcher will describe the effectiveness of the SBFP as employed in the research locale. Additionally, Key informant interview with the selected representatives of the identified groups of stakeholders was conducted to provide qualitative support to the claims of the study. Since this study used the KII as the principal mode of data gathering among the participants, a semi structure interview guide was used. The said interview shall be composed of 7-10 questions that were patterned to achieve the objectives of this research conduct. However, the researcher has the leeway to ask a follow up questions given the goal of the research is not yet clarified to the respondents.Meanwhile, the secondary data such as the baseline and endline data of the respondents’ nutritional status were taken from the Nutrition Coordinator of the school. Mean and t-test was used to analyze the data.Results revealed that the nutritional status of the pupils were below normal despite of the efforts in giving supplement and dietary assistance of the school through the conduct of feeding program hence the very purpose of the program in providing complete meals and enhancing the nutrition of these pupils were not thoroughly achieved.The mean of pupils’ baseline and end line data shows a highly significant difference on the baseline and endline data results for the pupils’ BMI with a P-value of 0.000 and t-value of -3.570.This implies that the results of the BMI of the pupil beneficiaries differ significantly before and after the 120 days feeding program. This means that there was a change and movement in the nutritional status of the pupils as the program was implemented.